Acoustic cues, not phonological features, drive vowel perception: Evidence from height, position and tenseness contrasts in German vowels - Llompart Garcia, Miguel; Reinisch, Eva (Journal of Phonetics, 2018)
Phonological features have frequently been singled out as the units of perception, especially for vowels. Evidence of the use of features has been provided for vowel height and vowel position, which have one acoustic correlate only. However, findings on acoustically complex features such as tenseness are less clear. The present study assessed the role of phonological features in perception using the selective adaptation paradigm. Selective adaptation effects on German vowel contrasts differing in vowel height (Experiment 1), position (Experiment 2) and tenseness (Experiment 3) were examined. We tested how the categorization of each vowel contrast was affected by adaptation to words containing vowels that differently resembled or diverged from the vowels in the critical contrast acoustically and in terms of their phonological feature specifications. Results showed that selective adaptation patterns could be predicted by the vowels' phonological features for the height and position contrasts, but not for the tenseness contrast. However, adaptation patterns for the latter can be explained by the relationship between adaptors and continuum endpoints in each of the relevant acoustic cues to the contrast. This suggests that vowel perception may be dependent on these acoustic cues rather than phonological features.
Keywords: Vowels; Pre-lexical units; Phonological features; Acoustic cues; Speech perception; Selective adaptation

Aptitude and experience as predictors of grammatical proficiency in adult Greek-English bilinguals - Prela, Leonarda; Llompart, Miquel; Dabrowska, Ewa (Frontiers in Psychology, 2022)
It has been shown that individuals exhibit great variability in second language (L2) ultimate attainment. Some speakers reach native-like proficiency, others only achieve a rudimentary command and many lie in the middle. Individual differences research has partly attributed different degrees of L2 attainment to (language) aptitude. Initially considered irrelevant for first language (L1) acquisition, aptitude was viewed as a compensatory ability for adults' disadvantage in L2 learning. In this line of thought, adults and children are viewed as fundamentally different and rely on different language learning mechanisms. However, aptitude might not be so irrelevant for the L1. Together with input the two factors are found to account for individual differences not only in L2 but also L1 development. Recent research has specifically shown that native grammatical attainment may be modulated by aptitude and input. In this respect, the aim of the current study is to examine the effects of these two predictors (namely input and aptitude) on both L1 and L2 grammatical attainment in the same speakers. Our participants (N = 75) were all native speakers of Greek who learned English as a foreign language in their home country and immigrated to the United Kingdom in adulthood (mean age of arrival = 27.3, SD = 6.4). Grammatical proficiency was measured through a grammaticality judgement task administered in both the L1 and the L2. Aptitude was measured through the Sentence Pairs task (based on the Words In Sentences test from the MLAT battery). Amount of input was measured using the traditional measure, length of residence (LoR) and a new cumulative measure that spanned across the participants' life. The two measures were pitted against each other in the analysis. We found robust effects of aptitude in both the L1 and the L2, with the effect being even stronger for the L1. As expected, our new cumulative measure of exposure proved to be a better predictor of individual differences in grammatical proficiency. Last but not least, the effects of input were larger for the L2 than the L1.
CRIS-Team WoS Importer:2023-01-20

Articulatory Information Helps Encode Lexical Contrasts in a Second Language - Llompart Garcia, Miguel; Reinisch, Eva (Journal of Experimental Psychology-Human Perception and Performance, 2017)
The present study examined whether obtaining additional articulatory information about the sounds of a difficult second-language contrast (English /E/-/ae/ for German speakers) could help nonnative listeners to encode a lexical distinction between novel words containing these two categories. Novel words (e.g., tenzer-tandek) were trained with different types of input and their recognition was tested in a visual-world eye-tracking task. In Experiment 1, a baseline group was exposed to the words audio-only during training, whereas another group additionally saw videos of the speaker articulating the target words. In Experiment 2, listeners were asked to repeat the target words themselves as part of their training. It was found that both audiovisual input and word repetition during training resulted in asymmetric fixation patterns at test: Words containing /E/ were recognized more readily than those with /ae/, mirroring the recognition asymmetry reported for real English words. This asymmetry was not present for the audio-only group, in which target words with the two vowels were fixated similarly. The results suggest that articulatory knowledge, acquired through both passive exposure to visual information (Experiment 1) and active production (Experiment 2), can help distinguishing words with difficult foreign sounds.
Keywords: second language; perception-production interface; speech perception; eye-tracking; lexical processing

Beyond age: exploring ultimate attainment in heritage speakers and late L2 learners - Prela, Leonarda; Dabrowska, Ewa; Llompart Garcia, Miguel (Frontiers in Psychology, 2024)
According to the Critical Period Hypothesis, successful language learning is optimal during early childhood, whereas language learning outside of this time window is unsuccessful. In this respect, early language acquisition is viewed as convergent and reliable but late acquisition is not. The present study revisits the idea of a critical period by investigating the grammatical attainment of early bilinguals/heritage speakers (HSs), late second/foreign language (L2) learners, and comparable groups of monolinguals by testing Greek-English bilinguals in the two languages they speak by means of a grammaticality judgment task. Our findings show that in English, HSs performed on par with monolinguals, both groups surpassing the late L2 learners, who performed about 2 SDs below the HSs and the monolinguals. In Greek, late L2 learners and monolinguals exhibited comparable performance, contrasting sharply with the HSs’ significantly lower proficiency, which was on average about 5 SDs below the late L2 learners and the monolinguals. Consequently, our results show that the performance gaps between HSs and Greek monolinguals/late L2 learners were more pronounced than the differences between late L2 learners and English monolinguals/HSs, suggesting that the early bilinguals’ success in English may come at the expense of their heritage language (Greek). Furthermore, we observe substantially more individual variation within HSs in their heritage language than within the late L2 learners for their second language. Thus, testing bilinguals in both of their languages allows us to unveil the complexity of grammatical ultimate attainment and prompt a re-thinking of age as the major determining factor of (un)successful attainment.
CRIS-Team Scopus Importer:2024-08-30
Keywords: bilingualism; grammar; heritage language acquisition; late bilinguals; second language acquisition; ultimate attainment

Can adults learn L2 grammar after prolonged exposure under incidental conditions? - Kenanidis, Panagiotis; Dabrowska, Ewa; Llompart Garcia, Miguel; Pili-Moss, Diana (PLoS ONE, 2023)
While late second language (L2) learning is assumed to be largely explicit, there is evidence that adults are able to acquire grammar under incidental exposure conditions, and that the acquisition of this knowledge may be implicit in nature. Here, we revisit the question of whether adults can learn grammar incidentally and investigate whether word order and morphology are susceptible to incidental learning to the same degree. In experiment 1, adult English monolinguals were exposed to an artificial language (Kepidalo) that had case marking and variable word order: a canonical Subject-Object-Verb order and a non-canonical Object-Subject-Verb. In a five-session online study, participants received vocabulary training while being incidentally exposed to grammar, and completed a series of picture-selection and grammaticality judgment tasks assessing grammatical knowledge. Despite extensive exposure to input, and although performance on vocabulary increased significantly across sessions, learners’ grammatical comprehension showed little improvement over time, and this was limited to Subject-Object-Verb sentences only. Furthermore, participants were better at detecting word order than case marking violations in the grammaticality judgment tasks. Experiment 2 further increased the amount of incidental exposure whilst examining native speakers of German, which exhibits higher morphological richness. Testing was followed by a post-test metalinguistic awareness questionnaire. Although greater learning effects were observed, participants continued to have difficulties with case marking. The findings also demonstrated that language outcomes were modulated by learners’ level of metalinguistic awareness. Taken together, the results of the two experiments underscore adult learners’ difficulty with case marking and point towards the presence of a threshold in incidental L2 grammar learning, which appears to be tightly linked to prior first language experience. In addition, our findings continue to highlight the facilitative role of conscious awareness on L2 outcomes.
CRIS-Team Scopus Importer:2023-08-11

Differential positional neutralization of back vowels in two Majorcan Catalan sub-dialects - Llompart Garcia, Miguel; Simonet, Miquel (Proceedings of the 18th International Congress of Phonetic Sciences, 2015)
The present paper explores the patterns of unstressed vowel reduction affecting the three back vowels of Catalan: /ɔ/, /o/ and /u/. In particular, we examine two reduction patterns found in the Catalan dialect spoken on the island of Majorca: (i) the general Majorcan pattern according to which /ɔ/ and /o/ merge to [o] in unstressed position and /u/ remains different (as [u]), and (ii) a pattern found only in one small village on the island of Majorca, Sóller, according to which /ɔ/, /o/ and /u/ all merge to [u]. By means of an acoustic study, the present paper establishes that the traditional impressionistic descriptions of these sub- dialects of Catalan with respect to their back vowels are correct and that these processes are thus best described as categorical, phonological (rather than gradient, phonetic) processes.
Keywords: unstressed vowel reduction; positional neutralization; back vowels; Majorcan Catalan

Explicit but Not Implicit Memory Predicts Ultimate Attainment in the Native Language - Llompart Garcia, Miguel; Dabrowska, Ewa (Frontiers in Psychology, 2020)
The present paper examines the relationship between explicit and implicit memory and ultimate attainment in the native language. Two groups of native speakers of English with different levels of academic attainment (i.e., high vs. low) took part in three language tasks which assessed grammar, vocabulary and collocational knowledge, as well as phonological short-term memory (assessed using a forward digit-span task), explicit associative memory (assessed using a paired-associates task) and implicit memory (assessed using a deterministic serial reaction time task). Results revealed strong relationships between phonological short-term memory and explicit associative memory on the one hand and the three language tasks on the other hand, and no relation between linguistic performance and implicit memory. Taken together, these results cast doubts on the common assumption that L1 grammar learning depends almost entirely on implicit memory and align with the claims of usage-based models of language acquisition that grammatical and lexical knowledge depend on the same cognitive mechanisms.
CRIS-Team Scopus Importer:2020-10-23
Keywords: declarative/procedural model; explicit memory; implicit memory; individual differences; ultimate attainment; usage-based models

Free Allophonic Variation in Native and Second Language Spoken Word Recognition: The Case of the German Rhotic - Llompart, Miquel; Eger, Nikola Anna; Reinisch, Eva (Frontiers in Psychology, 2021)
The question of how listeners deal with different phonetic variant forms for the same words in perception has sparked great interest over the past few decades, especially with regard to lenited and regional forms. However, the perception of free variant forms of allophones within the same syllable position remains surprisingly understudied. Because of this, in the present study, we investigate how free allophonic variation in the realization of the German rhotic (/r/) impacts spoken word recognition for native German listeners and two groups of non-native listeners (French and Italian learners of German). By means of a visual-world eye-tracking task, we tested the recognition of spoken German words starting with /r/ when the rhotic was produced either as the more canonical variant, the uvular fricative [(Figure presented.)] which is considered the German standard, or as an alveolar trill [r], a common realization in the south of Germany. Results showed that German listeners were more efficient at recognizing /r/-initial words when these were produced with the uvular fricative than with the alveolar trill. French listeners did not differ from German listeners in that respect, but Italian listeners showed exactly the opposite pattern: they showed an advantage when words were produced with the alveolar trill. These findings suggest that, for native listeners, the canonicity of the variant form is an important determiner of ease of recognition, even in the absence of orthographic or perceptual motivations for the primacy of canonical variants for this particular example of variation. For non-native listeners, by contrast, results are better explained by the match of the different allophones to the canonical realization of /r/ in their native language than by the status or frequency of the allophones in the non-native language itself.
CRIS-Team Scopus Importer:2021-12-17
Keywords: allophonic variation; German; phonetic variants; rhotics; second language; speech perception; spoken-word recognition; visual-world eye-tracking

Imitation in a second language relies on phonological categories but does not reflect the productive usage of difficult sound contrasts. - Llompart Garcia, Miguel; Reinisch, Eva (Language and Speech, 2019)

La «R Francesa» En Sóller (Mallorca) y su relación con la adquisición de L1 y L2 en hablantes bilingües catalanodominantes - Llompart Garcia, Miguel (Estudios de Fonetica Experimental, 2013)
Keywords: Bilingualism; Alveolar trill; Manner of articulation; Dorsalization; Place of articulation; Phonetic interference; Sóller

Lexical and Phonetic Influences on the Phonolexical Encoding of Difficult Second-Language Contrasts: Insights From Nonword Rejection - Llompart Garcia, Miguel (Frontiers in Psychology, 2021)
Establishing phonologically robust lexical representations in a second language (L2) is challenging, and even more so for words containing phones in phonological contrasts that are not part of the native language. This study presents a series of additional analyses of lexical decision data assessing the phonolexical encoding of English /ε/ and /æ/ by German learners of English (/æ/ does not exist in German) in order to examine the influence of lexical frequency, phonological neighborhood density and the acoustics of the particular vowels on learners’ ability to reject nonwords differing from real words in the confusable L2 phones only (e.g., *l[æ]mon, *dr[ε]gon). Results showed that both the lexical properties of the target items and the acoustics of the critical vowels affected nonword rejection, albeit differently for items with /æ/ → [ε] and /ε/ → [æ] mispronunciations: For the former, lower lexical frequencies and higher neighborhood densities led to more accurate performance. For the latter, it was only the acoustics of the vowel (i.e., how distinctly [æ]-like the mispronunciation was) that had a significant impact on learners’ accuracy. This suggests that the encoding of /ε/ and /æ/ may not only be asymmetric in that /ε/ is generally more robustly represented in the lexicon than /æ/, as previously reported, but also in the way in which this encoding takes place. Mainly, the encoding of /æ/ appears to be more dependent on the characteristics of the L2 vocabulary and on one’s experience with the L2 than that of its more dominant counterpart (/ε/).
CRIS-Team Scopus Importer:2021-06-25
Keywords: L1-accented input; L2 lexicon; lexical decision; lexical representation; nonword rejection; phonolexical encoding; second language learning; speech perception

Lexically driven selective adaptation by ambiguous auditory stimuli occurs after limited exposure to adaptors - Llompart Garcia, Miguel; Casillas, Joseph V. (Journal of the Acoustical Society of America, 2016)
Limited exposure to ambiguous auditory stimuli results in perceptual recalibration. When unambiguous stimuli are used instead, selective adaptation (SA) effects have been reported, even after few adaptor presentations. Crucially, selective adaptation by an ambiguous sound in biasing lexical contexts had previously been found only after massive adaptor repetition [Samuel (2001). Psychol. Sci. 12(4), 348-351]. The present study shows that extensive exposure is not necessary for lexically driven selective adaptation to occur. Lexically driven selective adaptation can arise after as few as nine adaptor presentations. Additionally, build-up course inspection reveals several parallelisms with the time course observed for SA with unambiguous stimuli. (c) 2016 Acoustical Society of America

Lexical representations can rapidly be updated in the early stages of second-language word learning - Llompart Garcia, Miguel; Reinisch, Eva (Journal of Phonetics, 2021)
Encoding second-language (L2) phonological contrasts into lexical representations is known to be challenging above and beyond the perceptual difficulties that these contrasts may entail. In two experiments, this study assessed the effect of form-focused training during word learning on the lexical encoding of the English /ɛ/-/æ/ contrast into novel L2 minimal pairs (e.g., tendek-tandek) by German learners of English. More specifically, we investigated whether the point in time in which form-focused training is administered (i.e., very first presentation vs. after one training session) determines learners’ success at distinguishing the two vowels in the novel words. In Experiment 1, only native English tokens were presented whereas, in Experiment 2, productions by a fellow German-accented learner of English were also included. Results revealed an early benefit of phonologically-focused training on lexical encoding and novel word recognition (Experiment 1) that nonetheless appeared to be constrained by the demands of the task and the properties of the input presented (Experiment 2). Most importantly, however, learners’ ultimate word recognition performance provided evidence that early lexical representations can rapidly be updated to reflect improvements in phonological knowledge.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Word learning; Lexical representations; Accented speech; Phonological acquisition; Minimal pairs; Speech perception; Second language learning

Literacy-related differences in morphological knowledge: A nonce-word study - Dabrowska, Ewa; Pascual, Esther; Macías-Gómez-Estern, Beatriz; Llompart, Miquel (Frontiers in Psychology, 2023)
Using a nonce-word inflection task, we examine the morphosyntactic productivity of adult native speakers of Spanish who are either beginning to learn to read and write (semi-literates) or have acquired literacy in late adulthood (late-literates), as well as age-matched controls (high-literates). High-literates consistently provided the appropriate form more often than late-literates, who in turn were better than semi-literate participants. Crucially, group interacted with person, number, and conjugation, such that the between-group differences were larger for the less frequent cells in the paradigm, indicating that literacy-related differences are not merely a consequence of the high-literacy group being more engaged or test-wise. This suggests that the availability of written representations may facilitate the acquisition of certain aspects of grammar. We also observed vast individual differences in productivity with inflectional endings. These results add to the growing body of research which challenges the assumption that all native speakers converge on the same grammar early in development.
CRIS-Team Scopus Importer:2023-05-26
Keywords: imperfect; individual differences; literacy; morphological productivity; preterite; Spanish; verbal morphology/derivation

Phonetic categorization ability and vocabulary size contribute to the encoding of difficult second-language phonological contrasts into the lexicon - Llompart Garcia, Miguel (Bilingualism-Language and Cognition, 2020)
This study investigated the contribution of second-language (L2) phonetic categorization abilities and vocabulary size to the phonolexical encoding of challenging non-native phonological contrasts into the L2 lexicon. Two groups of German learners of English differing in L2 proficiency (advanced vs. intermediate) participated in an English lexical decision task including words and nonwords with /É/ and /æ/ (/æ/ does not exist in German), an /É/-/æ/ phonetic categorization task and an English vocabulary test. Results showed that the effects of phonetic categorization and vocabulary size on lexical decision performance were modulated by proficiency: categorization predicted /É/-/æ/ nonword rejection accuracy for intermediate learners, whereas vocabulary did so for advanced learners. This suggests that sufficient phonetic identification ability is key for an accurate phonological representation of difficult L2 phones, but, for learners for whom robust phonetic identification is already in place, their ultimate success is tightly linked to their vocabulary size in the L2.
CRIS-Team Scopus Importer:2020-11-27
Keywords: L2 lexicon; L2 phonology; phonological representations; second language acquisition; speech perception

Redundancy can hinder adult L2 grammar learning: evidence from case markers of varying salience levels - Kenanidis, Panagiotis; Llompart, Miquel; Fernández Santos, Sara; Dabrowska, Ewa (Frontiers in Psychology, 2024)
Grammatical redundancy is a widespread feature across languages. Although redundant cues can be seen to increase the complexity and processing burden of structures, it has been suggested that they can assist language acquisition. Here, we explored if this learning benefit can be observed from the very initial stages of second language (L2) acquisition and whether the effect of redundancy is modulated by the perceptual salience of the redundant linguistic cues. Across two experiments, three groups of adult native speakers of English were incidentally exposed to three different artificial languages; one that had a fixed word order, Verb-Object-Subject, and two in which thematic role assignment was additionally determined by a low-salient (Experiment 1) or a high-salient (Experiment 2) redundant case marker. While all groups managed to learn the novel language, our results pointed towards a hindering role of redundancy, with participants in the non-redundant condition achieving greater learning outcomes compared to those in both redundant conditions. Results also revealed that this impeding effect of redundancy on L2 learners can be attenuated by the salience of the redundant cue (Experiment 2). In conjunction with earlier findings, the present results suggest that the effect of redundancy on L2 acquisition can be differentially manifested depending on the stage of L2 development, learners’ first language biases and age.
CRIS-Team Scopus Importer:2024-06-14
Keywords: artificial language learning; grammar; redundancy; salience; second language acquisition

Robustness of lexical representations relates to phonetic flexibility for difficult second language sound contrasts - Llompart Garcia, Miguel; Reinisch, Eva (Bilingualism-Language and Cognition, 2019)

Stressed postverbal pronominals in Catalan - Nadeu, Marianna; Simonet, Miquel; Llompart Garcia, Miguel (Probus, 2017)
Majorcan Catalan postverbal pronominal elements are typically described as being prominent due to stress shift from their host. This study sheds light on the prosodic phonology of these pronouns through the analysis of duration, vowel quality, and f0 in verb + pronominal sequences, which are compared to a baseline condition without pronominals and to the same sequences in a Catalan variety without stress shift. Our results show acoustic differences in the realization of pronominals in these varieties. The duration and vowel quality patterns are consistent with the stress shift account of postverbal pronominals in Majorcan Catalan. Analysis of f0 contours also reveals phonological differences across varieties. Whereas stressed postverbal pronominals are not rare in Romance, Majorcan Catalan is one of a much reduced number of varieties within the Romance domain, where the attachment of a pronominal element to a host triggers "true" stress shift rather than an additional prominence on the pronominal element, like Sardinian or Neapolitan.
Keywords: stress shift; Catalan; postverbal pronominals; clitics; prosody

Subject-verb order variation with unaccusative verbs of change of location in Mexico and Southern Arizona - Llompart, Miguel (Studies in Hispanic and Lusophone Linguistics, 2016)
The subjects of unaccusative verbs of change of location (e. g., llegar, venir) may appear in pre-verbal and post-verbal position. However, most syntactic accounts of word order in Spanish suggest that VS is the canonical order for these verbs. This claim has been supported by some experimental data, but further insight on the mechanisms underlying this particular instance of variation can still be gained from its study from a variationist, corpus-based perspective. We investigate the SV-VS alternation in the spontaneous oral discourse of two populations, monolingual Spanish speakers from Mexico City and Spanish-English bilingual speakers from Southern Arizona. Multivariate analyses reveal that the informative load of the subject, the animacy of the subject, verbal tense and aspect, and the presence or absence of an initial modifier, in this order, condition word order selection. The results also show that bilingual speakers from Southern Arizona are less flexible than monolinguals speakers in assigning word order to unaccusative verbs of change of location when the subject does not introduce new information, favoring SV almost categorically. A possible cause for this dissimilar behavior is the influence of English, where unaccusative verbs tend to appear pre-verbally, on the Spanish of these bilinguals.
Keywords: word order; unaccusatives; subject position; change-of-location verbs; spoken corpora

The Impact of Free Allophonic Variation on the Perception of Second Language Phonological Categories - Reinisch, Eva; Juhl, Katharina I.; Llompart Garcia, Miguel (Frontiers in Communication, 2020)
When learning the phonological categories of a second language (L2), learners have to deal with phonetic variation. For instance, allophonic variant forms have to be recognized as the same phoneme. A minimal pair identification task was used to assess how late Spanish learners of German perceive the phonological /r/-/h/ contrast. German /r/ was realized as one of three allophones ([r], [R], [ʁ]) that vary in phonetic similarity to /h/ as well as to the typical phonetic form of Spanish /r/ (i.e., [r]). Results showed that learners were very good at identifying all German variant forms (>90% correct). However, [ʁ], which is phonetically closest to German /h/ and furthest from Spanish /r/, was identified significantly worse than [r] and [R]. Relating these results to a cross-language perception task where learners were asked to map the German allophones of /r/ and the phoneme /h/ to different L1 phonological categories further showed that those learners were best at identifying words with [ʁ] who consistently matched it to a single L1 category. Surprisingly this category did not always have to be the phonologically matching Spanish /r/. We conclude that phonological and phonetic relations between the learners' L1 and L2 are important in identifying allophones of the same L2 category.<br

The phonological form of lexical items modulates the encoding of challenging second-language sound contrasts - Llompart Garcia, Miguel; Reinisch, Eva (Journal of Experimental Psychology-Learning Memory and Cognition, 2020)
The present study investigated whether the ability to encode the sounds of difficult second-language (L2) contrasts into novel nonnative lexical representations is modulated by the phonological form of the words to be learned. In 3 experiments, German learners of English were trained on word-picture associations with either novel minimal pairs only differing in the difficult /epsilon/-/ae/ contrast (Experiments 1 and 2; e.g., tendek-tandek) or pairs that additionally differed in their second syllables (Experiment 3; e.g., tenzer-tandek). Word recognition was assessed by means of a visual-world eye-tracking task. We asked whether learners would be more successful at encoding a distinction between the 2 vowels in the minimal-pair than in the nonminimal-pair items because of the central role of the contrast for accurate word learning with minimal pairs. Results from eye-fixation analyses at test showed that learners recognized /epsilon/-items faster than /ae/-items when they were minimal pairs and these pairs had already appeared together on the screen on a number of training trials (Experiment 1 vs. 2). This asymmetry could not be replicated with nonminimal pairs (Experiment 3). In line with previous studies, the asymmetry in Experiment 2 is taken as evidence of lexical separation for /epsilon/ and /ae/. Accordingly, we argue that exposure to the minimal-pair stimuli highlighted the challenging distinction by enhancing listeners' attention to the critical sounds and conclude that the encoding of difficult L2 contrasts into the lexicon is more likely when the phonological form of the words emphasizes relevant phonological differences that may otherwise remain unnoticed.
CRIS-Team WoS Importer:2020-07-31

Unstressed Vowel Reduction Across Majorcan Catalan Dialects: Production and Spoken Word Recognition - Llompart Garcia, Miguel; Simonet, Miquel (Language and Speech, 2018)
This study investigates the production and auditory lexical processing of words involved in a patterned phonological alternation in two dialects of Catalan spoken on the island of Majorca, Spain. One of these dialects, that of Palma, merges /?/ and /o/ as [o] in unstressed position, and it maintains /u/ as an independent category, [u]. In the dialect of Soller, a small village, speakers merge unstressed /?/, /o/, and /u/ to [u]. First, a production study asks whether the discrete, rule-based descriptions of the vowel alternations provided in the dialectological literature are able to account adequately for these processes: are mergers complete? Results show that mergers are complete with regards to the main acoustic cue to these vowel contrasts, that is, F1. However, minor differences are maintained for F2 and vowel duration. Second, a lexical decision task using cross-modal priming investigates the strength with which words produced in the phonetic form of the neighboring (versus one's own) dialect activate the listeners' lexical representations during spoken word recognition: are words within and across dialects accessed efficiently? The study finds that listeners from one of these dialects, Soller, process their own and the neighboring forms equally efficiently, while listeners from the other one, Palma, process their own forms more efficiently than those of the neighboring dialect. This study has implications for our understanding of the role of lifelong linguistic experience on speech performance.
Keywords: Unstressed vowel reduction; incomplete neutralization; acoustic phonetics; phonological processing; cross-modal priming; spoken-word recognition; Catalan dialects